Longitudinal impact of cross-clamp duration on postoperative sleep disturbance and quality of life in elderly cardiac surgery patients: a secondary analysis of the MINDDS trial - Grace E. Namirembe; Jamie Sparling; Alexis Novak; Ariel Mueller; Julia Bertsch; Kwame Wiredu; Jason Z. Qu; M. Brandon Westover; Timothy T. Houle; Oluwaseun Akeju (Frontiers in Anesthesiology)
ObjectivesThis study aimed to assess the enduring impact of cross-clamp duration on postoperative sleep disturbance and functional outcomes (up to 180 days) in cardiac surgery patients.DesignThis is a secondary analysis of data from a randomized, double-blind trial comparing dexmedetomidine to placebo for delirium prevention (Minimizing ICU Neurological Dysfunction with Dexmedetomidine-induced Sleep).SettingData from patients recruited at a tertiary medical center in Boston, Massachusetts, between March 2017 and February 2022 were analyzed in January 2024.ParticipantsThe study included 394 patients aged ≥60 who underwent cardiac surgery with cardiopulmonary bypass.InterventionsThe primary exposure was cross-clamp time, while secondary exposures included surgical type [isolated coronary artery bypass graft (CABG) or not] and dexmedetomidine randomization.Measurements and main resultsThe primary outcome was sleep quality, assessed using the PROMIS Sleep Disturbance questionnaire at 30, 90, and 180 days postoperatively. Secondary outcomes encompassed cognitive function and health-related quality of life in various domains. Sleep quality, measured by PROMIS scores, showed improvement over time, and did not differ based on cross-clamp duration (MD 0.74 points, 95% CI: −0.57, 2.07), procedure type (MD 2.14 points, 95% CI: 0.29, 3.99), or dexmedetomidine (MD 0.9 points, 95% CI: −1.33, 1.5). However, isolated CABG patients reported sleep disturbance at all time points. Notably, extended cross-clamp time (>90 min) significantly worsened the trajectories of mental health (90-day: MD −2.37 points, 95% CI: −4.35, −0.39; 180-day: MD −2.68 points, 95% CI: −4.62, −0.73) and applied cognition (180-day: MD: −2.59 points, 95% CI: −4.49, −0.68).ConclusionRegardless of the duration of the cross-clamp, sleep quality tends to improve over time following cardiac surgery. However, cross-clamp times that last longer than 90 min have been identified as a risk factor for self-reported declines in mental health and applied cognition.